Dravidian and Altaic parts of the body 2. Hair, feather - J. Vacek Charles (Acta Mongolica, 2006)
This paper is another contribution to the Dravidian and Altaic lexical parallels. The questions of the phonetic form of the lexemes have been discussed in several of my latest papers on the subject and may be consulted there (Vacek 2001 ff., especially 2004b or 2006a) and in the book on ‘water — viscosity — cold’ (Vacek 2002). More details about the phonological relationship on the basis of phonetic ‘models’ as a part of a continuum may be referred to in thosé publications. Further related questions may also be consulted in some works of K. V. Zvelebil (especially 1990, 1991, both with further references). This is the second paper discussing the etyma concerning the ‘body’ (cf. Vacek 2005c, which contains some further remarks on the parts of the body mentioned on previous occasions). The following two etyma display an interesting semantic variation. Originally I had intended to separate the lexemes designating ‘feather’ from those designating ‘hair’, but it became obvious that this is almost a regular semantic extension not only in Dravidian but also in some Altaic etyma.